2015
DOI: 10.1016/j.pmrj.2015.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Receiving a Prosthesis for Adults With Above‐Knee Amputations in a Well‐Defined Population

Abstract: Background Prior studies have identified age as a factor in determining an individual’s likelihood of receiving a prosthesis following a lower limb amputation. These studies are limited to specific subsets of the general population and are unable to account for pre-amputation characteristics within their study populations. Our study seeks to determine the effect of pre-amputation characteristics on the probability of receiving a prosthesis for the general population in the United States. Objective Identify p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 25 publications
(27 reference statements)
0
29
0
1
Order By: Relevance
“…Several studies investigated prosthesis use and prosthesis fitting rates in lower limb amputees [29][30][31][32][33][34][35][36]. However, most studies [30][31][32][34][35][36] had a small sample size and/or did not report outcomes for different amputation levels. Davie-Smith et al [29] as well as Resnik et al [33] found fit rates in transfemoral amputees of 21.6% and 19.2%, respectively.…”
Section: Epidemiologymentioning
confidence: 99%
“…Several studies investigated prosthesis use and prosthesis fitting rates in lower limb amputees [29][30][31][32][33][34][35][36]. However, most studies [30][31][32][34][35][36] had a small sample size and/or did not report outcomes for different amputation levels. Davie-Smith et al [29] as well as Resnik et al [33] found fit rates in transfemoral amputees of 21.6% and 19.2%, respectively.…”
Section: Epidemiologymentioning
confidence: 99%
“…Individuals with prosthesis were 84% less likely to die within the first 2.5 years of the index date compared with those who did not receive a prosthesis (Table ). As reported previously, all individuals who received a prescription for prosthesis received one within the first 7 months of amputation (prosthesis fitting occurred an average of 105 days postamputation) . In a sensitivity analysis, we eliminated the individuals who died within the first 7 months of index date (N = 41) and the protective effect of prosthesis on death hazard rate disappeared.…”
Section: Resultsmentioning
confidence: 99%
“…As reported previously, all individuals who received a prescription for prosthesis received one within the first 7 months of amputation (prosthesis fitting occurred an average of 105 days postamputation). 28 In a sensitivity analysis, we eliminated the individuals who died within the first 7 months of index date (N = 41) and the protective effect of prosthesis on death hazard rate disappeared. This indicates that the effect of prosthesis is likely confounded by indication for amputation and illness severity, and we are unable to explain the relationship with our current construct given that patients needed to be healthy enough to qualify for prosthesis receipt.…”
Section: Prosthesis Effectmentioning
confidence: 99%
“…Findings showed instances of prosthetic prescription where the cause of amputation, comorbidities, age and general physical condition were seemingly not taken into consideration. Evidence on the negative effect of these variables on a person’s ability to function with a prosthesis is clear from these studies (Davie-Smith et al 2017 ; Mundell et al 2016 ; Resnik & Borgia 2015 ; Roffman et al 2014 ; Schoppen et al 2003 ; Yilmaz et al 2016 ). The tool, which takes these factors into consideration, might provide valuable guidance in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…The AMP assesses sitting, standing, balance and locomotion. The ability to balance on the remaining leg has a strong correlation with prosthetic ability and use (Raya et al 2010 ; Schoppen et al 2003 ), whereas the use of mobility-assistive devices before the amputation correlates with decreased prosthetic provision (Mundell et al 2016 ) and function (Roffman, Buchanan & Allison 2014 ). However, aspects such as age (Davie-Smith et al 2017 ; Mundell et al 2016 ; Resnik & Borgia 2015 ; Schoppen et al 2003 ; Yilmaz et al 2016 ), cause of amputation (Mundell et al 2016 ), comorbidities (Resnik & Borgia 2015 ), cognition (Mundell et al 2016 ) as well as the condition of the remaining and residual limbs (Raya et al 2010 ; Roberts et al 2006 ) also influence prosthetic functioning.…”
Section: Introductionmentioning
confidence: 99%